Pemberdayaan Komunitas Sekolah melalui Program SIGAP ( Siswa Sehat, Gizi Aktif, dan Peduli) Berbasis Edugame dalam Pencegahan Obesitas di SD Xaverius 4 Palembang - Eva Elfrida Pardede; Devieka Rama Dhany; Devi Ardila; Dindi Paizer (Lembaga Pengembangan Kinerja Dosen, 2025)
Childhood obesity is a growing public health problem in Indonesia. This increases the risk of developing non-communicable diseases at an early age. The SIGAP (Healthy, Actively Nutritional, and Caring Students) Community Service Program is an educational initiative aimed at improving nutritional literacy and strengthening the role of the school community in preventing childhood obesity. This activity was conducted at Xaverius 4 Elementary School, Palembang, involving 62 students, 15 teachers, and 8 parents (members of the school committee). The implementation method includes the preparation of the SIGAP module as an activity guide, education to students about balanced nutrition and obesity prevention in children packaged with educational games namely Puzzle Isi Piringku, Detektor Makanan and Senam SIGAP as well as the formation of Duta SIGAP as peer educators in schools. Workshops for parents and teachers focused on increasing understanding about obesity prevention in children, a shared commitment to creating a healthy school environment and supporting healthy living behaviors at home and at school. Evaluation was carried out through pre-test and post-test questionnaires in the domains of knowledge, attitudes and behavior. The results showed an increase in students' knowledge, attitudes, and behaviors regarding balanced nutrition and physical activity, the formation of SIGAP Ambassadors, and the strengthening of collaboration between teachers and parents to maintain healthy and balanced eating habits and physical activity. The SIGAP program demonstrated that a participatory approach based on educational games is effective in fostering a healthy lifestyle and supporting obesity prevention in children.